Global, regional, and national burden of anxiety disorders during the perimenopause (1990–2021) and projections to 2035 - Ying Zhang; Ting-Ting Hu; Yong-Ran Cheng; Zhi-Fen Zhang; Jun Su (BMC Women's Health)
Abstract Purpose Perimenopause is associated with an increased risk of anxiety disorders, largely due to hormonal changes affecting the body’s regulatory feedback mechanisms. This study aims to provide a comprehensive analysis of the global burden of anxiety disorders among perimenopausal women. Methods Data from the 2021 Global Burden of Disease (GBD) database were utilized to assess disability-adjusted life years associated with anxiety disorders linked to perimenopause. We calculated trends using the estimated average percent change, and future projections were made using the Bayesian age–period–cohort model to estimate disability-adjusted life year trends for anxiety disorders from 2022 to 2035. Results Between 1990 and 2021, the global age-standardized disability-adjusted life year rate for anxiety disorders among perimenopausal women increased from 625.51 (95% uncertainty interval: 429.1–891.09) to 677.15 (95% uncertainty interval: 469.45–952.72), indicating a rising trend with an estimated average percent change of 0.081 (95% confidence interval: 0.0043–0.143). Regional differences were noted, with anxiety disorder burdens varying across areas with different sociodemographic index levels. Projections suggest that by 2035, the global burden of anxiety disorders in perimenopausal women will rise to 1,180.43 per 100,000, a 40.67% increase compared with 2021 levels. Conclusion The burden of anxiety disorders during perimenopause is a growing global concern, with a significant increase anticipated in the coming years. Targeted prevention and intervention strategies are urgently needed to mitigate this rising burden and improve mental health outcomes during perimenopause.